PERAN GURU DALAM MENGINTEGRASIKAN ARTIFICIAL INTELLIGENCE UNTUK MENANAMKAN NILAI-NILAI AKHLAK MULIA PADA SISWA SEKOLAH DASAR - Afizah Afizah; Fathma Anggraita; Muhammad Alhalim; Syastri Ulya; Sukran Sukran (Study program PGSD FKIP Universitas Bung Hatta, 2026)
This study aims to critically explore the urgency of teachers’ roles in integrating Artificial Intelligence (AI) to cultivate noble moral values among elementary school students within the Indonesian educational context. Using a qualitative approach through literature analysis, this study examines relevant international journal articles, Indonesian Sinta-accredited national journals, academic books, reports published by international organizations, and conference proceedings addressing AI in education, character education, and elementary school learning. The analysis was conducted through systematic processes of literature identification, selection, reduction, synthesis, interpretation, and comparison to develop a comprehensive conceptual understanding. The findings indicate that AI has considerable potential to enhance learning quality by supporting personalized instruction, differentiated learning, timely feedback, and students’ digital literacy development. Nevertheless, the successful implementation of AI largely depends on teachers’ competencies in integrating technology with sound pedagogical practices, digital ethics, and character education. This study proposes a conceptual model for AI integration based on noble moral values, positioning teachers as the primary agents who guide the use of AI as a pedagogical partner rather than a substitute for educators. The proposed model is expected to serve as a conceptual reference for strengthening Pancasila and Civic Education as well as character education in Indonesian elementary schools amid the ongoing digital transformation.